Efektivitas Model Pembelajaran Numbered Head Together (NHT) dengan Pendekatan Saintifik terhadap Minat dan Hasil Belajar Biologi Materi Virus Kelas X MIPA 2 SMAN 15 Bone - Adhelina, Adhelina; Hartati, Hartati; Azis, Andi Asmawati (Universitas Negeri Makassar, 2021)
ABSTRACTThis study is a pre-experiment with a one group pretest-posttestdesign research design that aims to determine the effectiveness of learning NHT model with a scientific apporoach to student’s biology learning interest and outcomes. The sample of this study was selected randomly and selected in class X MIPA 2 as the experimental group. Data collection techniques through the provision of multiple choice test a description test before (pretest) and after (posttest) learning and giving learning interest questionnaires before (pretest) and after (posttest). Data analysis technique used is descriptive and inferential statistical analysis with t-test. The results showed that (1) The effectiveness of the cooperative learning NHT model with a scientific apporoach to student biology learning interest, which is effective. (2) The effectiveness of the cooperative learning model NHT with a scientific apporoach to student biology learning outcomes which is effective. (3) Numbered Head Together (NHT) cooperative learning model with a scientific apporoach an effective be applied with the efectiveness criteria of learning implementation fulfilled, the activities of students are ini a very good category, the response of positive students as well as interest and biology learning outcomes of students increases.